Analysis Of Student’s Diagnostic Ability in Electricity And Magnetism’s Course Based on Quizziz Platform.: 1*Rifda Nur Hikmahwati Arif, 2Sitti Rahma Yunus, 3Nurul Fakhrannisa, 4Salma Samputri, 5Rifda Mardian Arif - Rifda Nur Hikmahwati Arif; Sitti Rahma Yunus; Nurul Fakhrannisa; Salma Samputri; Rifda Mardian Arif (PT ARRUS Intelektual Indonesia, 2024)
This study aims to analyse the diagnostic ability of ICP science students FMIPA UNM in the Electricity and Magnetism course. This research uses descriptive research with a Quizizz-based qualitative approach. The sampling technique used was purposive sampling. The data collection technique used in this study was a multiple choice diagnostic test accessed through the Quizizz platform online. The data analysis technique used is descriptive statistics (frequency, percentage, and average) and item analysis (index of difficulty and differentiating power of the questions. Quizizz-based diagnostic tests for electrical and magnetic topics are effective enough to evaluate students' initial abilities. Most questions have a moderate difficulty level and sufficient to good differentiating power; however, some questions have low or negative differentiating power and need to be corrected. The results showed that students' diagnostic ability in Electricity And Magnetism’s Course using quizziz platform was at 5,0 score which in a low category. This research serves as a basis for the development of better diagnostic tests to achieve learning objectives.